Language Representation of Covid-19 Report on CNN Indonesia Online Media and its Utilization as a Critical Reading Enrichment Book - Rahman, Sarimagfirah; Saleh, Muhammad; Idawati, Idawati (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
This study aims to describe the form and form of linguistic representation in the CNN Indonesia news text by using social change analysis from Norman Fairclough. The focus of this research is text analysis, text production, and sociocultural analysis with data in the form of grammatical features. This research is a discourse analysis study in the form of critical discourse analysis (AWK). The data source of this research is CNN Indonesia online media which contains words, phrases, clauses, and sentences. The research data was obtained by using documentation, reading, and note-taking techniques. The results show that there are grammatical features which include: (1) modality, (2) negation, (3) sentence mode, (4) transitivity, (5) personal pronouns, and (6) passivity which represents the form of linguistic representation through power in in the news text. Judging from the production of the text, it is shown that the producer of the text in presenting the news cannot be separated from the aspect of domination and power, either power or domination by groups or individuals. In addition, the power in the text serves to strengthen the position of a subject in the text so that the reader is focused on the discourse conveyed by the author of the text. Furthermore, as an implication of the research results, a critical reading enrichment book was compiled.